Maternal dietary and environmental factors associated with infant circadian rhythm, growth, and temperament: Research protocol for a prospective cohort study - Kok, Ee Yin; Kaur, Satvinder; Mohd Shukri, Nurul Husna; Abdul Razak, Nurliyana; Takahashi, Masaki (SAGE Publications, 2024)
Introduction: Emerging evidence has been explored to determine the factors affecting the development of infant circadian rhythm. While fetal programming happens during the pregnancy period, external environmental cues and infant nutritional programming can have substantial effects on the infant circadian rhythm. Understanding prenatal and postnatal factors determining infant circadian rhythm can improve future interventions in optimizing maternal and infant health. Methods: This is a prospective observational cohort study, targeting 216 pregnant women from government maternity clinics in Kuala Lumpur, Malaysia. Pregnant women will be recruited at third trimester (baseline), and follow up at 3 months, and 6 months. A subsample will be collected for salivary cortisol analysis to determine circadian rhythm of the mother and infant at third trimester and 3 months. Data of eating misalignment, light exposure, chronotype, infant temperament, sleep quality, and mood will be collected via validated questionnaires. Anthropometric data and birth outcomes will be collected from antenatal and postnatal health records. Summary: Studies on infant circadian rhythm development have yet to be explored and established, hence this study presents a novel approach to identify the factors from prenatal to postnatal periods on infant circadian rhythm and its influence on growth and temperament. Findings from this study will provide insights in the critical timing which has larger effects on infant circadian rhythm development for future interventions to be conducted. © The Author(s) 2024.